Temperatura, escarificação mecânica e substrato na germinação de sementes das palmeiras juçara e açaí - Beckmann-Cavalcante, Márkilla Z.; Pivetta, Kathia F. L. [UNESP]; Iha, Liriane Laguardia [UNESP]; Takane, Roberto J. (Revista Brasileira de Ciencias Agrarias, 2012)
The propagation of 'juçara' and 'açaí' is done by seeds, but there is a great desuniformity in the germination process. In this way, the objective of this study was to verify the effect of temperature, mechanical scarification and substrate on seed germination of both species. Two experiments were conducted in a completely randomized design, with four replications each consisting of 25 seeds. The first was conducted with 14 treatments in factorial scheme 7 x 2, seven temperatures (20, 25, 30, 35, 20-30 and 25-35 °C and natural condition), with and without mechanical scarification. The second was constituted of eight treatments in factorial scheme 4 x 2, four substrates (sand, vermiculite, coconut fiber and soil + manure), with and without mechanical scarification. Seeds of 'juçara' palm present the highest mean percentage and germination speed index in alternating temperatures of 20-30 and 25-35 °C and natural condition and in substrates sand, vermiculite and coconut fiber. Temperatures of 30, 35, 20-30 and 25-35 °C and natural condition in all substrates tested were the most favorable condition for 'açai' seeds. The scarification of the seeds was favorable to the germination process of 'juçara' whereas the seeds of açaí does not need to be scarified.
Temperature, mechanical scarification and substrate on seed germination of 'juçara' and 'açaí' palm
Keywords: Euterpe edulis; Euterpe oleraceae; Germinative process; Physic dormancy; Euterpe